Promoting smoking cessation during pregnancy: A feasibility and pilot trial of a digital storytelling intervention delivered via text‐messaging. Issue 7 (July 2022) - King, Emma; Cheyne, Helen; Abhyankar, Purva; Elders, Andrew; Grindle, Mark; Hapca, Adrian; Jones, Claire; O'Carroll, Ronan; Steele, Mary; Williams, Brian
Highlights: Text-messaging has potential to deliver interventions to harder to reach groups. Our digital storytelling intervention had positive feedback from participants. Behaviour change techniques aimed at smoking behaviour were embedded in the story. Difficulty in contacting and following up participants made study methods unfeasible. Research is required to optimise methods for reaching pregnant smokers. Abstract: Objective: Smoking during pregnancy causes risks to mother and infant health. We investigated the feasibility and likely success of SKIP-IT, a narrative and picture-based smoking cessation intervention delivered via text messages. Methods: A feasibility and pilot trial. We aimed to recruit 70 pregnant women who smoked, randomised to usual care alone, or usual care and the SKIP-IT intervention, between 12 weeks of pregnancy and 6 weeks post due-date. Outcomes assessed were recruitment, retention, acceptability of, and engagement with the intervention, smoking behaviour, intentions, perceived risk, and self-efficacy. Results: Of 312 women initially approached by smoking cessation services only 54 (17%) agreed to be contacted by the research team. Twenty were then either ineligible or uncontactable and 28 (82%) participated. Most women reported texts to be entertaining and helpful. The proportion of women not smoking at follow-up was lower in the intervention group, but numbers were too small to draw conclusions about effectiveness. Conclusion: The intervention was acceptable, but difficulty in making initial and follow-up contacts meant our methods were unfeasible for a larger trial. Practice implications: Digital Storytelling interventions could help women quit smoking, but further research is required to identify alternative methods for studies with pregnant women who smoke.